Ideal Parent Figure method in the treatment of complex posttraumatic stress disorder related to childhood trauma: a pilot study. Issue 1 (1st January 2017) - Parra, Federico; George, Carol; Kalalou, Khalid; Januel, Dominique
ABSTRACT: Background : There is a consensus within the trauma field for the necessity of a three-phase treatment programme for complex posttraumatic stress disorder (CPTSD). This pilot study focuses on the stabilisation phase, the goal of which is the development of psychological resources and the reduction of disabling symptoms. Objective : To test the efficacy of the Ideal Parent Figure (IPF) method as a stabilization treatment for CPTSD patients with a history of childhood trauma. Method : The sample was comprised of 17 adults with a history of childhood trauma concomitant with CPTSD symptoms consulting at a clinic in France. Participants enrolled in a 5-week psychotherapy programme based on the IPF method, a semi-structured visualization programme designed to treat attachment disturbances. Measures of DESNOS symptoms, psychological symptoms, quality of life, and adult attachment were administered pre- and posttreatment as well as at 8-month follow-up. Results : A significant decrease in symptom severity and attachment traumatization and a significant increase in quality of life were found, both with medium-to-large effect sizes. The 8-month follow-up assessment showed outcome stability. Conclusions : These results suggest that treating attachment disturbances directly with an approach akin to the Ideal Parent Figure method may lead to fast and stable improvement for individuals with CPTSD.